Beijing from below : stories of marginal lives in the capital's center - Evans, Harriet (Duke University Press, 2020)
"In BEIJING FROM BELOW, Harriet Evans weaves together oral history, archival research, and ethnographic knowledge to tell the story of the residents of Dashalar, an under-resourced Beijing neighborhood adjacent to Tiananmen Square. In popular thinking about China, the Mao and post-Mao development of Beijing's cityscape has often been understood as the result of teleological progression and entrance to a market economy. However, what is lost in such narratives are the effects that development has had on Beijing's urban underclass; for example, during the 1950s, construction projects throughout Beijing led to the mass displacement of many urban dwellers, and current development projects still require the forced movement of residents. In this book, which focuses on events from the 1950s onwards, Evans attends to the experiences of the working-class residents of Dashalar, using their own oral testimony and state records to understand how they interpret and relate to the changing city. In this regard, BEIJING FROM BELOW is a study on the interwoven nature of subaltern lives and state authority, as it seeks to discern subalternity within dominant state systems by shedding light on Beijing's overlooked residents. Through deft readings of the historical record, Evans also reveals how Dashalar's residents have been left out of the historical record, thereby providing an alternative historiography of Beijing outside of the progressive version offered by the People's Republic. This book is organized around the stories of individual families, and each chapter is followed by a critical interlude analyzing the main themes of the family's story. Through these narratives, Evans draws out historical and theoretical topics such as: reworking traumas from the past in service of surviving the present; the experiences of migrant families in an already under-resourced neighborhood; and the negotiations families and individuals are willing to make to find stability. This book will be of interest to students and scholars of China and Chinese history, anthropology, history, and subaltern studies"--